Caught in the Same Frame? The Language of Evidence‐based Policy in Debates about the Australian Government 'Intervention' into Northern Territory Aboriginal Communities. (7th June 2013) - Partridge, Emma
Abstract This article examines ongoing contestation surrounding the policies of the Federal government's 'Intervention' in Indigenous communities in Australia's Northern Territory. It highlights how the paradigm of 'evidence‐based policy' has been used by both the government and its critics, suggesting this commonality of language is worthy of reflection. Cautioning against an over‐reliance on the rationalist framework of 'evidence‐based policy', it draws on literature that problematizes this idea and insists on the inherently contested and political nature of the relationship between knowledge, evidence and policy‐making. It concludes by pointing to alternative strategies for improving Indigenous policy that risk being overlooked by a focus on 'evidence‐based policy' as a prescriptive ideal.